2016
DOI: 10.1165/rcmb.2016-0236rc
|View full text |Cite
|
Sign up to set email alerts
|

An Inhaled Inhibitor of Myristoylated Alanine-Rich C Kinase Substrate Reverses LPS-Induced Acute Lung Injury in Mice

Abstract: Intratracheal instillation of bacterial LPS is a well-established model of acute lung injury (ALI) and/or acute respiratory distress syndrome (ARDS). Because the myristoylated alanine-rich C kinase substrate (MARCKS) protein is involved in neutrophil migration and proinflammatory cytokine production, we examined whether an aerosolized peptide that inhibits MARCKS function could attenuate LPS-induced lung injury in mice. The peptide, BIO-11006, was delivered at 50 mM via inhalation either just before intratrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…The marked decrease in nucleated cells in BALf after treatment with PIP-2 suggests that this function of ROS is important for the recovery from lung injury. In that respect, a peptide inhibitor of the myristoylated alanine-rich C kinase substrate (Marcks) protein also protects against lung injury with LPS in mice [44]. Although this latter peptide has not been shown to inhibit NOX2 activation, its effects may be mediated through altered cellular motility that prevents PMN influx into the lung.…”
Section: Discussionmentioning
confidence: 99%
“…The marked decrease in nucleated cells in BALf after treatment with PIP-2 suggests that this function of ROS is important for the recovery from lung injury. In that respect, a peptide inhibitor of the myristoylated alanine-rich C kinase substrate (Marcks) protein also protects against lung injury with LPS in mice [44]. Although this latter peptide has not been shown to inhibit NOX2 activation, its effects may be mediated through altered cellular motility that prevents PMN influx into the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the application of LPS can induce inflammation in mice (Zhou et al, 2013; Yin et al, 2016). The purpose of this study was to explore the effect of pregnancy ‐related gynaecological diseases on anxiety‐related behaviours in offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with aerosolized BIO-11006 at 0, 4, 12, 24, and even 36 hours after LPS instillation reversed the disease process: Mouse behavior returned to normal after two treatments 12 hours apart with the inhaled peptide after LPS injury, whereas control LPS-instilled animals treated with PBS only remained moribund. Histological appearance of inflammation, BAL fluid protein concentrations, leukocyte and neutrophil numbers, KC (keratinocyte chemoattractant; CXCL1, mouse IL-8 equivalent) and TNF-a gene and protein expression, and NF-kB activation were all significantly attenuated by inhaled BIO-11006 at all time points (23). The fact that the treatment was effective as long as 36 hours after administration of LPS to the mice suggests that inhaled MARCKS inhibitors could be an effective treatment for patients who present with already-active ARDS.…”
Section: Ardsmentioning
confidence: 94%
“…Structure MARCKS binds and cross-links actin, bridges calmodulin (CaM) and PKC signaling, and sequesters phosphatidylinositol 4,5-bisphosphate (PIP 2 ) in the plasma membrane (1)(2)(3)(4)(5)(6). Associated with cellular events that require actin, including adhesion, migration and exocytosis (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), it is involved in pulmonary disorders such as chronic obstructive pulmonary disease (COPD), asthma, acute respiratory distress syndrome (ARDS) and lung cancer (12,17,(20)(21)(22)(23). In 1982, Wu and colleagues described an "87 kD" PKC substrate protein that is known today as "MARCKS" (6,24).…”
Section: Properties Of Marcks Proteinmentioning
confidence: 99%
See 1 more Smart Citation